Toma Loa Se Banari as Educational Social Capital: An Ethnopedagogical Study in Tidore: Toma Loa Se Banari sebagai Modal Sosial Pendidikan: Studi Etnopedagogi di Tidore - Bakri Ismail; Non Drakel; Jamin Safi (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
The life philosophy of the Tidore community reflects a profound perspective on shaping a complete human identity, both morally and socially. One of the core values embraced is Toma Loa Se Banari, which emphasizes the importance of being a righteous and well-behaved individual in all aspects of life. These values are embodied in attitudes of integrity, togetherness, and social responsibility. This study aims to explore how such principles are utilized as a form of social capital within the educational process through an ethnopedagogical approach rooted in local culture. Using a descriptive qualitative method, the research observes how Tidore society transmits cultural values through daily social interactions, informal learning within families and communities, as well as formal education in schools. The findings indicate that consistent integration of local values into the education system can effectively shape students’ character in a holistic way. Therefore, strengthening culture-based education becomes a crucial step in enriching the curriculum while preserving the unique cultural identity of the Tidore community.